Bilateral oblique facial clefts, rudimentary eyes and hydrocephalus in an aborted equine foetus. (22nd March 2017) - Agerholm, JS; Pedersen, HG; McEvoy, FJ; Heegaard, S
Contents: Knowledge of congenital malformations and their causes in horses is generally sparse. Such conditions require more scientific attention to improve their diagnostics and inform prevention strategies. Here, a unique syndrome of bilateral oblique facial clefts (meloschisis), rudimentary eyes and hydrocephalus is reported in an equine foetus spontaneously aborted at gestation day 224. The cause of abortion was considered to be intrauterine death caused by umbilical cord torsions and subsequent compromised blood flow, but the aetiology of the malformation could not be determined. A detailed history, which includes exposure to a range of pharmaceutical compounds during the early stages of pregnancy, is provided and emphasizes the need for accurate recording of treatments in pregnant animals.